Avaliação da despalha mecânica em linhagem experimental submetida à dessecação - Frigoni, André Sellaro (2009)
To investigate how desiccation influences hybrid corn (Zea mays L.) during husk removal, two experiments were carried out at Santa Bárbara Farm, in Vicentinópolis, state of Goiás, during 2007/08 growing season, with an experimental line (female parent) provided by Syngenta Seeds Ltd. Experiments were defined by the type of desiccant application: one as corn-ear directed, the other as whole plant application. Both experiments were performed in a completely randomized design, with five replications per treatment. Desiccant treatments consisted of different timings of application, established by the kernel milk-line movement, and the control (no desiccation). The number of lodged plants and ears was assessed in the field. Seeds loss was assessed during its processing. And seed quality was assessed in laboratory by the following determinations: thousand seed weight, slight and severe mechanical damages, rotten and cracked seeds, germination and vigor. Results led to the conclusion that desiccation did not made husk removal easier and, thus, did not reduce loss of seeds.